The complemented mutant complΔBcstc7niaD, in the STC7 of Botrytis cinerea led to the characterization of 11, 12, 13-tri-nor-eremophilenols derivatives. (January 2022) - Suárez, Ivonne; Pinedo, Cristina; Aleu, Josefina; Durán-Patrón, Rosa; Macías-Sánchez, Antonio J.; Hernández-Galán, Rosario; Collado, Isidro G.
Abstract: Botrytis cinerea has high potential for the production of specialized metabolites. The recent resequencing of the genome of the B05.10 strain using PacBio technology and the resulting update of the Ensembl Fungi (2017) database in the genome sequence have been instrumental in identifying new genes that could be involved in secondary metabolism. Thus, a new sesquiterpene cyclase (STC) coding gene ( Bcstc7 ) has been included in the gene list from this phytopathogenic fungus. We recently constructed the null and complement transformants in STC7 which enabled us to functionally characterize this STC. Deletion of the Bcstc7 gene abolished (+)-4- epi -eremophilenol biosynthesis, and could then be re-established by complementing the null mutant with the Bcstc7 gene. Chemical analysis of the complemented transformant suggests that STC7 is the principal enzyme responsible for the key cyclization step of farnesyl diphosphate (FDP) to (+)-4- epi -eremophil-9-en-11-ols. A thorough analysis of the metabolites produced by two wild-type strains, B05.10 and UCA992, and the complemented mutant compl ΔBcstc7 niaD, revealed the isolation and structural characterization of six 11, 12, 13-tri- nor -eremophilene derivatives, in addition to a large number of known eremophilen-11-ol derivatives . The structural characterization was carried out by extensive spectroscopic techniques. The biosynthesis of these compounds is explained by a retroaldol reaction or by dehydration and oxidative cleavage of C11–C13 carbons. This is the first time that this interesting family of degraded eremophilenols has been isolated from the phytopathogenous fungus B. cinerea . Graphical abstract: Image 1 Highlights: Two wild strains and the mutant compl ΔBcstc7 niaD of Botrytis cinerea were studied. Six new cryptic metabolites with skeletons of tri- nor -eremophilenes were identified. The biosynthesis of 11, 12, 13-tri- nor -4- epi -eremophil-9-enols has been proposed.